The vault : an Inspector Wexford novel - Rendell, Ruth, 1930- (New York : Scribner, 2011)
Former Chief Inspector Wexford returns from retirement to solve a most unlikely case: the mystery of who killed the three people whose corpses were last seen at the bottom of a coal hole in A Sight for Sore Eyes (1999). In the decade since Franklin Merton left St. John's Wood in 1998, Orcadia Cottage has changed hands twice by the time Martin Rokeby, who wants to make room for an amphora his wife Anne found in Florence, pulls up a manhole cover in his backyard and shines a light down a dark shaft to reveal not only the three victims from the author's earlier tale but a fourth, much more recently dead than the others but equally beyond identification. Det. Supt. Thomas Ede, of Cricklewood, is getting nowhere with the case, so he invites Reg Wexford, who's retired to Hampstead Heath, to join him as an unpaid consultant. Accompanying Ede and his sergeant, Lucy Blanch, on interviews, he ventures several guesses as to the identities of the dead: Merton's vanished second wife, Harriet? The young man seen driving an Edsel and heard calling himself Keith Hill? His uncle, from whom he may have taken his name and much more? Orcadia neighbor Mildred Jones's cleaner Vladlena, who memorably burned the shirt of her then husband Colin? He watches as he is proved right or wrong, but does not simply watch, for trauma and tragedy are about to visit Wexford's own family in equally unnerving ways
Keywords: Wexford, Inspector (Fictitious character) -- Fiction; Police -- England -- Sussex -- Fiction; Sussex (England) -- Fiction